2022
DOI: 10.3390/cells11040606
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Stem Cell Transplantation in Multiple Myeloma: Where Are We and Where Do We Want to Go?

Abstract: The introduction of high-dose therapy in the 1990s as well as the development of drugs such as thalidomide, lenalidomide, and bortezomib in the 2000s led to an impressive improvement in outcome of patients with multiple myeloma (MM) eligible for autologous stem cell transplantation (ASCT). Clinical trials conducted in the first ten years of the twenty-first century established as standard therapy for these patients a therapeutic approach including induction, single or double ASCT, consolidation, and maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 96 publications
0
14
1
2
Order By: Relevance
“…Similarly, patients in our study population who received ASCT also had better survival than patients who did not receive ASCT, and such benefits remained significant among patients with R-ISS II/III disease. With a median follow-up time of 58.7 months, the PFS and OS for our study population who did and did not receive ASCT were slightly lower compared with the results from prior clinical trial observations with a similar duration of follow-up 25 . In agreement with a previous study 29 , patients who achieved ≥ CR after ASCT demonstrated better survival than patients who only achieved VGPR or PR after ASCT.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Similarly, patients in our study population who received ASCT also had better survival than patients who did not receive ASCT, and such benefits remained significant among patients with R-ISS II/III disease. With a median follow-up time of 58.7 months, the PFS and OS for our study population who did and did not receive ASCT were slightly lower compared with the results from prior clinical trial observations with a similar duration of follow-up 25 . In agreement with a previous study 29 , patients who achieved ≥ CR after ASCT demonstrated better survival than patients who only achieved VGPR or PR after ASCT.…”
Section: Discussioncontrasting
confidence: 76%
“…In agreement with previous studies [21][22][23] , our study showed a greater treatment response in patients with novel agents treatment (e.g., PI-, PI+IMiD-, or IMiD-based regimens) compared to patients who received conventional therapy. In addition, ASCT is recommended for transplant-eligible NDMM patients for survival benefits, even among patients with HRCA [24][25][26][27][28] . Similarly, patients in our study population who received ASCT also had better survival than patients who did not receive ASCT, and such benefits remained significant among patients with R-ISS II/III disease.…”
Section: Discussionmentioning
confidence: 99%
“…16 There is no standard storage time for refrigerated PBSC in studies with fresh autologous transplantation of MM, ranging from 24 to 144 h. 3,[18][19][20] Most studies comparing fresh and cryopreserved infusion have maintained fresh cells up to 48 h 3,4,11 and the increase of storage time must be clinically validated. 10 In our study, all fresh transplanted patients received PBSC after 72 h of cool storage. Our previous laboratorial study substantiated our clinical validation, considering evaluation of graft quality in different storage times and conditions; we have previously validated the best conditions for maintenance of PBSC in refrigerated storage.…”
Section: Resultsmentioning
confidence: 98%
“…There is no standard storage time for refrigerated PBSC in studies with fresh autologous transplantation of MM, ranging from 24 to 144 h 3,18–20 . Most studies comparing fresh and cryopreserved infusion have maintained fresh cells up to 48 h 3,4,11 and the increase of storage time must be clinically validated 10 . In our study, all fresh transplanted patients received PBSC after 72 h of cool storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation